2022
DOI: 10.3390/cancers14246132
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Therapeutic Target for Small-Cell Lung Cancer: Tumor-Associated Repair-like Schwann Cells

Abstract: Small-cell lung cancer (SCLC), representing 15–20% of all lung cancers, is an aggressive malignancy with a distinct natural history, poor prognosis, and limited treatment options. We have previously identified Schwann cells (SCs), the main glial cells of the peripheral nervous system, in tumor tissues and demonstrated that they may support tumor spreading and metastasis formation in the in vitro and in vivo models. However, the role of SCs in the progression of SCLC has not been investigated. To clarify this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…We recently reported that SCs can promote the proliferation and motility of SCLC cell lines in vitro (Cao et al, 2022). To determine the effect of SCs on NSCLC cells and investigate the involvement of SC‐derived extracellular vesicles, we harvested SC‐conditioned medium (SC‐CM) and obtained exosome‐free SC‐CM by size exclusion chromatography and ultracentrifugation (SC‐CM fraction S150).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that SCs can promote the proliferation and motility of SCLC cell lines in vitro (Cao et al, 2022). To determine the effect of SCs on NSCLC cells and investigate the involvement of SC‐derived extracellular vesicles, we harvested SC‐conditioned medium (SC‐CM) and obtained exosome‐free SC‐CM by size exclusion chromatography and ultracentrifugation (SC‐CM fraction S150).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous animal studies revealed that SCs, as the principal glial cells of the PNS securing neuronal survival and function, could accelerate lung adenocarcinoma growth and spreading by inducing macrophage polarization and EMT via chemokine production (Zhou et al, 2018; Zhou et al, 2020). Recently, we reported that tumor‐associated SCs may stimulate the viability and motility of SCLC cells (Cao et al, 2022). However, the mechanisms underlying human SC protumorigenic activity are mostly unknown.…”
Section: Discussionmentioning
confidence: 99%
“…SCs were detected in the lung tumors and in the tumor surrounding area both in experimental animals and human specimens ( Silva et al, 2019 ; Cao et al, 2022 ). Furthermore, the retrospective analysis of SC identification in NSCLC tissues comprising 90 cases of adenocarcinoma and 51 cases of squamous cell carcinoma revealed higher levels of SCs in cancerous tissues compared to adjacent tissues ( Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that identified intratumoral SC-associated molecules may be used as systems biomarkers for screening in perineural invasion of lung cancer or for potential therapeutic purposes ( Silva et al, 2019 ). Importantly, new data focusing on the ability of human TA-SCs to regulate the functional activity of human SCLC cell lines in vitro revealed that TA-SCs upregulated longevity, proliferation, migration, and invasiveness of tumor cells ( Cao et al, 2022 ). In vivo studies confirmed these findings by demonstrating that SCs promote the growth of SCLC in mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation